Dietary patterns and colorectal adenomas in Lynch syndrome. Issue 3 (17th December 2012) - Botma, Akke; Vasen, Hans F. A.; van Duijnhoven, Fränzel J. B.; Kleibeuker, Jan H.; Nagengast, Fokko M.; Kampman, Ellen
Abstract BACKGROUND: Patients with Lynch syndrome (LS) have a high risk of developing colorectal cancer due to mutations in mismatch repair genes. Because dietary factors, alone and in combination, influence sporadic colorectal carcinogenesis, the association of dietary patterns with colorectal adenomas in LS patients was assessed. METHODS: In the GEOLynch cohort of 486 persons with LS, dietary information was collected, using a food frequency questionnaire. Dietary pattern scores were obtained by principal components analysis. Hazard ratios (HR) between dietary patterns and colorectal adenomas were calculated using Cox regression models. Robust sandwich variance estimates were used to control for dependency within families. Final models were adjusted for age, sex, smoking habits, colorectal adenoma history, and extent of colon resection. RESULTS: During a median follow‐up of 20 months, colorectal adenomas were detected in 58 persons. Four dietary patterns were identified: a "Prudent, " "Meat, " "Snack, " and "Cosmopolitan" pattern. Individuals within the highest tertile of the "Prudent" pattern had a HR of 0.73 (95% confidence interval [CI], 0.32‐1.66) for colorectal adenomas, compared with the lowest tertile. Those with high "Meat" pattern scores had a HR of 1.70 (95% CI, 0.83‐3.52). A high "Snack" pattern was associated with an increased risk of colorectal adenomas (HR, 2.16; 95% CI, 1.03‐4.49). A HR of 1.25 (95% CI, 0.61‐2.55) was observed for persons in the highest tertile of the "Cosmopolitan" pattern. CONCLUSIONS: These findings suggest that dietary patterns may be associated with development of colorectal adenoma in patients with Lynch syndrome. The directions of these findings are corroborative with those observed in studies investigating sporadic colorectal cancer. Cancer 2013. © 2012 American Cancer Society.